Developing children's food products - Kilcast, David; Angus, Fiona (Woodhead Pub., 2011)
Annotation The development of food and drink products for children and adolescents represents an expanding market sector, which has received little attention in the existing literature. In recognition of increasing concerns regarding diet and nutrition in children and their potential impact on nutrition-related health issues in later life, this book covers three broad aspects relating to developing childrens food products nutrition and health, childrens food choices, and the design and testing of food and drink products for children. Part one covers topical issues in pre-adult nutrition and health, such as nutritional requirements, fluid intake needs, diet and behavior and growing 20th century health problems such as childhood obesity and food allergies. Part two then focuses on childrens food choices, addressing food promotion and food choice in children and strategies that can be used to improve childrens food choices both inside and outside of the home. Finally, part three considers the design of food and drink products for children, with an emphasis on working with children and adolescents to design food and drink products, and how best to undertake consumer and sensory testing with children.
Keywords: Children -- Nutrition.; Food preferences in children.; Nutrition -- Requirements.; Children.; Food industry and trade.; Food preferences.; elektronické knihy; electronic books